Comparação entre duas técnicas de protração maxilar em indivíduos com fissura labiopalatina - Repeke, Daiana Broll (2019)
Unilateral cleft lip and palate (UCLP) is the most frequent deformity of non-syndromic oral cleft. Patients with UCLP presents deficiency of maxillary development in anteroposterior direction as a result of the primary surgeries (cheiloplasty and palatoplasty) performed in the first year of life. There are few articles comparing the new treatment protocol for maxillary protraction using bone-anchored maxillary protraction (BAMP) with the conventional maxillary traction protocol with facemask. This study aims to evaluate maxillary protraction with facemask and maxillary expansion and to compare with BAMP in patients with UCLP. 16 UCLP patients, who presented a class III skeletal pattern and a mean 9.5 years old, were treated with facemask; and 23 UCLP individuals were treated with BAMP, mean of 11.7 years old, also class III skeletal. Cone-beam computed tomography were obtained before (T1) and after treatment (T2) and twenty cephalometric variables were analyzed. Intergroup and intragroup comparisons were performed using independent t-test and paired t-test, respectively (p <0.05). The intergroup results showed similar anterior maxilla movement in both groups. A statistically lower SNB angle was observed in facemask group when compared to the BAMP group. Regarding the vertical positioning of the mandible, it was observed that in the group treated with BAMP the rotation happens counterclockwise. In addition, a lower incisors retroinclination was reported in facial mask treated group and a buccal inclination in the BAMP group. Thus, it was concluded that the two treatment protocols presented an effective sagittal maxillary advancement, with no difference between the groups.